Serviços de saúde mental para crianças e adolescentes: recomendações para o planejamento de políticas públicas de saúde mental - Graeff-Martins, Ana Soledade [UNIFESP] (2010)
Introduction There is clear evidence of social and economic impact of mental health disorders started in childhood and adolescence and of the inefficiency of health systems to deal with the problem in most countries. Public policies based on epidemiological data are urgently needed to promote greater access to services, coordination among the various sectors that receive children and adolescents with mental health problems and regular funding for systems. One of the key issues to be studied for planning policies in mental health of children and adolescents is access to mental health services and related factors. Objectives The aims of this study are: to review research findings on the prevalence of mental health services use by children and adolescents and factors associated; to describe the methodological problems of studies and propose a conceptual model to be used in future research; to estimate the prevalence of mental health services use and associated factors in a community sample of students; and to identify factors associated with the presence of components of mental health and the pattern of referral of students with problems in educational institutions from four localities in a state of southeastern Brazil. Recommendations for public policies on mental health for children and adolescents will be done. Methods 1) A systematic review of articles in the literature was performed, to identify studies that reported the prevalence of mental health services use in non-referred samples of subjects up to 18 years old. 2) A stratified random sample of 6986 students was assessed regarding mental health service use in school and out of school, sociodemographic factors, different levels of exposure to the attack, probable psychiatric diagnosis and having talked to parents, teachers and religious leaders about the attack. 3) Responsibles for all special schools and a random sample of regular schools in four areas of Rio de Janeiro State were interviewed about the presence of mental health professionals or procedures in the institutions and associated factors. Results 1) 174 full-text articles were examined, and 56 studies were included in this review. Great variability of mental health services use prevalence rates ! 5 was found. Factors related to services use were listed. 2) 17.1% of the sample had used mental health services, more in schools than out. Mental health service use in school was associated to having talked to teacher about the attack. Mental health service use out of school was associated to direct exposure to the attack, previous exposure to traumatic events, probable diagnosis of major depressive disorder and posttraumatic stress disorder and having talked to teacher and religious leader about the attack. 3) The presence of mental health professionals or procedures in schools seems to be associated to the area in which the institution is located, are more often found in nurseries and pre-schools and institutions that have professionals or procedures of other sectors of care (general health, justice and welfare). Referrals of students with mental health problems occur more frequently in schools with professionals or procedures of mental health, to the resources of the institution. Conclusions It is possible to establish a conceptual model for research on mental health services use by children and adolescents, and some methodological guidelines are suggested. Public policies on mental health of children and adolescents should include measures to promote training of professionals who are in frequent contact to children and adolescents, as teachers, pediatricians, family physicians, nurses, etc., and public awareness campaigns on children and adolescents mental health. The provision of mental health services in school environment should also be considered.